The Diversity of Soil Macrofauna on Agroforestry Teak (Tectona grandis) and Polynesian Arrowroot (Tacca leontopetaloides - Aji Winara (Jurnal Agroforestri Indonesia, 2018)
Teak and polynesian arrowroot is a new pattern of agroforestry to support food security of communities around forests in coastal areas. The presence of polynesian arrowroot under teak stands is not only expected to be food sources but also to provide ecological benefits for biodiversity, especially soil macrofauna. The study aims is to determine the diversity of soil macrofauna in teak and polynesia arrowroot agroforestry patterns. The study was conducted in Garut Regency in April 2017. The method used in this study was monolithic technique and analyzed by calculating diversity and richness index. The object was an agroforestry demonstration plot with three polynesia arrowroot spacings under 7-years-old teak stand and monoculture teak. The results showed that there were 5 soil macrofaunas in teak and polynesian arrowroot agroforestry which are from five families and five orders. The dominance order was coleoptera with Important Value Index (IVI) = 133.93% -157.78% and opisthophora with IVI = 103.51%. The diversity and richness of soil macrofauna in teak and polynesian arrowroot agroforestry patterns is low (H '= 0.28-0.55; R' = 0.87-1.48). Although agroforestry cultivation is carried out intensively, there is no difference in the diversity of soil macrofauna when compared to teak monoculture.